Graphic design in museum exhibitions : display, identity and narrative - Piehl, Jona (Abingdon, Oxon ; New York, NY : Routledge ; Taylor & Francis Group, 2021)
"Graphic Design in Museum Exhibitions offers an in-depth analysis of the multiple roles that exhibition graphics perform in contemporary museums and exhibitions. Drawing on a study of exhibitions that took place at the Victoria and Albert Museum, London, the Museum of London and the Haus der Geschichte, Bonn, Piehl brings together approaches from museum studies, design practice and narrative theory to examine museum exhibitions as multimodal narratives in which graphics account for one set of narrative resources. The analysis underlines the importance of aspects such as accessibility and at the same time problematises conceptualisations that focus only on the effectiveness of graphics as display device, by drawing attention to the contributions that graphics make towards the content on display and to the ways in which it is experienced in the museum space. Graphic Design in Museum Exhibitions argues for a critical reading of and engagement with exhibition graphic design as part of wider debates around meaning making in museum studies and exhibition-making practice. As such, the book should be essential reading for academics, researchers and students from the fields of museum and design studies. Practitioners such as exhibition designers, graphic designers, curators and other exhibition makers, should also find much to interest them in the book"--
1: Framing and reframing exhibition graphic design; 2: Exhibition graphics as means of display; 3: Exhibition graphics as expressions of institutional identity; 4: Exhibition graphics as visual content; 5: Exhibition graphics as resource of exhibition narration; 6: Negotiating the multiple roles of exhibition graphics; List of exhibitions and museums
Revision of the author's thesis (Ph.D.)--University of the Arts London, 2015, under the title: Reframing exhibition graphic design : an exploration of the multiple roles of graphic design and its impact on storytelling in museum exhibitions.
Includes bibliographical references and index.
in English.
Keywords: Museum exhibits -- Design; Commercial art -- Themes, motives; Design -- Graphics